Multiphoton Imaging of Tumor Biomarkers in situ Using Single-domain Antibodies Conjugated with Quantum Dots in a Set Orientation. (2016) - Sukhanova, Alyona; Hafian, Hilal; Turini, Marc; Chames, Patrick; Baty, Daniel; Pluot, Michel; Cohen, Jacques H.M.; Millot, Jean-Marc; Nabiev, Igor
Abstract: The use of photoluminescence (PL) probes in immunodiagnostic procedures requires highly specific and precise labeling of biomarkers and he tags whose PL is easily differentiable from that of the autofluorescence of cells in clinical specimens. Nanoprobes consisting of core/shell quantum dots (QDs), notably CdSe/ZnS ones, and single-domain antibodies (sdAbs) with PL excited in the multiphoton mode meet both requirements. These diagnostic nanoprobes are <12 nm in size, and their two-photon absorption cross section exceeds 49, 000 GM. Such nanoprobes, upon two-photon excitation (TPE) in near infrared region, provide precise fluorescent microscopic images of deep areas of tissue samples, the QD PL to autofluorescence intensity ratio being more than an order of magnitude higher than that for the one-photon mode of excitation.